2021
DOI: 10.1002/chem.202005283
|View full text |Cite
|
Sign up to set email alerts
|

Stimuli‐Responsive Self‐Sorting Hybrid Hydrogen‐Bonded/Metal‐Coordinated Cage

Abstract: The self‐assembly of a unique molecular container is reported: a hybrid hydrogen‐bonded/metal‐coordinated cage where both hydrogen‐bonding and metal‐coordination form the crucial part of the topology. The hybrid cage was prepared combining hydrogen‐bonded rosette motif and palladium(II)/platinum(II) coordination to a pyridine ligand. It was also shown that the hybrid cage could be prepared by integrative self‐sorting from simple components. For the first time the genuine dual character of the hybrid cage was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…95 The resultant covalent-supramolecular polymer was stiff and showed high damping capacity due to its network structure. Apart from the examples presented above, other orthogonal supramolecular interaction pairs were also well explored, including hydrophobic interaction/high affinity between fluorinated moieties, 96 hydrogen bond/hydrophobic interactions, 97 hydrogen bond/coordination bonds, 61,98 and hydrogen bond/ p-p interaction. 99 Meanwhile, some other strong interactions or driving forces could also be combined and utilized for constructing self-sorting systems, including crystallization of small molecules and macromolecules, 16 liquid crystalline ordering-driven assembly, 17,100-104 etc.…”
Section: Orthogonal Supramolecular Interactionsmentioning
confidence: 99%
“…95 The resultant covalent-supramolecular polymer was stiff and showed high damping capacity due to its network structure. Apart from the examples presented above, other orthogonal supramolecular interaction pairs were also well explored, including hydrophobic interaction/high affinity between fluorinated moieties, 96 hydrogen bond/hydrophobic interactions, 97 hydrogen bond/coordination bonds, 61,98 and hydrogen bond/ p-p interaction. 99 Meanwhile, some other strong interactions or driving forces could also be combined and utilized for constructing self-sorting systems, including crystallization of small molecules and macromolecules, 16 liquid crystalline ordering-driven assembly, 17,100-104 etc.…”
Section: Orthogonal Supramolecular Interactionsmentioning
confidence: 99%
“…Mukherjee et al constructed a complicated coordinated molecule by coordination-driven self-assembly of homometallic Pd/Pt-based s -triazine ligand as interlocked molecular cages [ 2 ]. Motloch et al reported the synthesis of the Pt(II)/Pd(II) complex with s -triazine-type ligands for the purpose of hydrogen bonded/metal-coordination hybrid [ 3 ]. Another representative example was designed, synthesized and characterized by He et al via self-assembly of supramolecular coordination complexes using platinum salt with two different types of pyridyl-derivatized ligands [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular containers and cages are hosts with three-dimensional cavities defined by their surrounding molecular frameworks, synthesized by linking together various subunits through covalent bonds or noncovalent interactions . Unlike molecular cages prepared using only nonlabile covalent bonds, those assembled with the aid of noncovalent interactions (e.g., metal chelation and hydrogen bonding) and dynamic covalent bonds are generally capable of undergoing exchange of their components in solution, allowing guests with sizes larger than any cavity openings to be entrapped and released, thereby allowing such systems to be used as guest preservers, transporters, or nanoflasks . Nevertheless, dynamic exchange creates challenges in the purification and characterization of molecular containers and their guest-incarcerated forms.…”
mentioning
confidence: 99%